Functional state of the circulatory and respiratory systems in highly qualified athletes when using hyperbaric oxygenation in training conditions in the middle mountain region - Ter-Akopov G.N. ,; Koryagina Yu.V. ,; Kushnareva Yu.V. ,; Nopin S.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study of the dynamics of the functional state of the circulatory and respiratory systems in highly qualified athletes using HBOT in training conditions in mid-mountains. Methods and structure of the study. The study of the effects of HBO in the training of athletes in mid-mountain conditions was carried out during training camps with 11 highly qualified female athletes at an altitude of 1240 meters in Kislovodsk, on Mount Maloe Sedlo. The course of HBOT procedures was carried out in a BaroOx 1.0 pressure chamber with the following parameters: excess pressure – 30 kPa, oxygen content – ​​93±2%, air flow – 45 l/min, compression/decompression rate – 6 kPa/min. The duration of one procedure is 30 minutes, the course is at least 7 procedures, 1 procedure per day. Results and conclusions. Positive effects of the use of HBOT in female athletes during training in mid-mountain mountains were observed after the course in terms of heart rate variability parameters in the form of an increase in parasympathetic activity, while after the 1st session the power indicators of very slow waves indicated a hyperadaptive reaction. After a course of 7 procedures, changes in central hemodynamics also occurred: vascular tone and blood pressure decreased. The general condition caused by increased tone of the parasympathetic part of the autonomic nervous system in women led to a relaxing effect, including on the respiratory muscles The results obtained allowed the authors to propose an effective strategy for training athletes in mid-altitude areas, designated as «Live high - train high, recover with additional oxygen». This method is recommended for general recovery of the body after a training day, micro- and mesocycle, and during the off-season training period.